GAMBARAN EFISIENSI PELAYANAN RAWAT INAP TERHADAP INDIKATOR GRAFIK BARBER JOHNSON DI RSUD KOTA BAUBAU TAHUN 2019 – 2021 - Mustika Mustika Nur Rahmi; Fitriani Fitriani; Taswin Taswin; Eky Endriana Amiruddin (Kampurui Jurnal Kesehatan Masyarakat, 2022)
ABSTRACT The efficiency level of the hospital is strongly influenced by the number of community visits related to the quality of service. Baubau City Hospital as a Covid-19 referral center, of course, has an effect on increasing the number of inpatient visits, especially Covid-19 patients who receive health services at Baubau City Hospital. The research uses a descriptive approach. The research location is the Baubau City Hospital in August - October 2021. The population is the daily census of inpatients from 2019 to the first semester of 2021. The data sources are Daily Census Data and Inpatient Patient Register Books and the Profile of Baubau City Hospital.                    Results show that the efficiency level of the Baubau City Hospital Inpatient Room Efficiency from 2019 to Semester I of 2021 is outside the Efficient area. Where the achievements in 2019 are 38.33% BOR, 3.32 days AVLOS, 5.36 days TOI and 42.01 times BTO. Achievements in 2020 are BOR 27.68%, AVLOS 3.31 days, TOI 8.64 days and BTO 30.62 times. The achievements of Semester 1 of 2021 are BOR 32.93%, AVLOS 3.27 days, TOI 6.16 days and BTO 19.06 times.                    The conclusion shows that the 2019 to 2021 BOR values ​​have not met the standard of 75%. AVLOS values ​​are standard (3-12 days). The TOI value has not met the standard (1-3 days). The BTO value in 2019 to 2020 has met the standard (>30 times), but in 2021 Semester I has not met the standard. So the Baubau City Hospital needs to increase patient visits and improve quality service facilities/infrastructure.